Tracing Eponymous Word Combinations in Education and Pedagogy - Vera Budykina; Oksana Polyakova (Estudios de Lingüística)
Currently, there is a significant focus on the exploration and classification of eponymous terminology across a range of fields of study. Scholars are particularly interested in the term’s foundation, theoretical underpinnings, and the lexicographic aspects of its application across various domains. Notably, eponymous terms are most prominent in medical, economic, political, historical, and technical fields. However, there is a need to broaden research efforts in pedagogy and education terminology, which includes several eponymous terms. The study was conducted following dictionary criticism principles and tackled the analysis of quantitative and qualitative data on eponymous phrases found in three English-language special dictionaries. The ultimate objective was determining the feasibility of including eponym terms in a dictionary. The research objectives were outlined to achieve this goal. The authors carefully selected and analysed the terminology, identifying corresponding semantic fields and conducting a structural and grammatical analysis of 93 eponymous phrases. They identified various semantic fields, such as “Diseases and Mental Disorders,” “Psychology and Psychological Expertise,” “Pedagogical Schools, Principles, and Educational Institutions,” “Educational Reforms,” and “Reports on Education,” among others, and provided commentary on the practicality of including eponymous terms in a dictionary of education. Research on eponyms has revealed that they share similar grammatical and nominative structures as non-eponymic terms, functioning as individual words and word groups. Typically, eponyms consist of two elements: a noun and an adjective or a noun and another noun. Anthroponyms –names derived from people – are often used in eponyms to describe the founders of pedagogical schools and trends, developers of psychological theories and testing methods, and scientists who have identified diseases and mental disorders requiring unique learning approaches. Additionally, eponyms may incorporate place names and names of literary or mythical characters, creating phrases like Pickwick Syndrome, Munchausen Syndrome, Summerhill School, and the Bologna Declaration. Furthermore, the primary eponymous trends within the semantic fields have been identified through a rigorous analysis of both quantitative and qualitative data. The findings align with the global trend observed at the study’s outset, where medical eponymy prevails. Therefore, terminologists and lexicographers must focus on the study of this eponymous terminology.